Collection development of electronic resources in management libraries of India. Issue 3 (4th July 2016) - Kaur, Manpreet; Walia, Paramjeet Kaur
Abstract : Purpose: The main purpose of this paper is to examine the current practices related to e-resource collection development in management libraries of India with special reference to the National Capital Region (NCR) of Delhi with some constructive suggestions for improvement in this area. Design/methodology/approach: A well-structured questionnaire was administered to the librarians of the nine management libraries under study. Findings: The management libraries are actively involved in building e-resource collection. The budget allocation for purchase of e-resources has increased progressively over the years in majority of the libraries. The factors that, to a great extent, affect selection of e-resources include quality, subject coverage, license agreements and vendor support. The study found that libraries associated with management institutions such as ABS, DMS-IITD, FMS, BIMECH and FSM need to add more management-related databases. Research limitations/implications: The paper restricts the study exclusively to e-resources as the type of material and the librarians of nine major management institutions of NCR of Delhi as the respondents in its scope of discussion. Practical implications: The study is of great importance to information professionals of similar management institutions in India. The recommendations made could also help solve some of the challenges that are being faced. Originality/value: Very little is known about the electronic resource collection development practices followed in management institutes' libraries of India owing to lack of significant research undertaken on the topic. This study is, therefore, significant because its findings fill up the existing knowledge gap in this area.